Implementation of Culturally Responsive Teaching in Private Islamic Education Learning through Action Research - Nabila Hasna Rafilah; Munawar Rahmat; Nurti Budiyanti (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This study aimed to describe the implementation of Culturally Responsive Teaching (CRT) in private Islamic Religious Education (IRE) tutoring, analyze students' responses, identify challenges encountered during implementation, and evaluate improvements in teaching practices through action research. This study employed a qualitative approach using the Kemmis and McTaggart Action Research model, which consisted of two cycles involving planning, action, observation, and reflection. The participants included an Islamic Religious Education tutor, 3–5 private tutoring students, and parents as supporting informants. Data were collected through observations, semi-structured interviews, documentation, and reflective journals, and were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings revealed that the implementation of CRT enhanced students' engagement, learning motivation, and self-confidence during the learning process. Students became more actively involved in connecting Islamic Religious Education content with their everyday experiences, while improvements introduced in the second cycle, including the use of more creative learning media and contextual examples, further optimized the learning process. Nevertheless, the effective implementation of CRT requires continuous professional development for tutors, particularly in understanding students' characteristics and designing culturally responsive learning experiences. Overall, CRT proved to be an effective pedagogical approach for creating more contextual, inclusive, and student-centered learning in private Islamic Religious Education tutorin